2001
DOI: 10.1073/pnas.171131398
|View full text |Cite
|
Sign up to set email alerts
|

Chiral exciton coupling of merocyanine dyes within a well defined hydrogen-bonded assembly

Abstract: Multichromophoric hydrogen-bonded assemblies 13⅐(BAR)6 are studied that bear a remarkably close resemblance to commelinin, a naturally occurring assembly responsible for an intense blue color of flowers. The incorporated chromophores exhibit a hypsochromic shift in the UV͞visible (Vis) absorption maximum (⌬ max ‫؍‬ 14 nm) compared with the free chromophores. In addition, the chiroptical properties of incorporated chromophores can be rationally controlled by changing the supramolecular chirality of the assembly… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

2
44
0

Year Published

2002
2002
2013
2013

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 58 publications
(46 citation statements)
references
References 24 publications
2
44
0
Order By: Relevance
“…[7] Other examples include merocyanine assemblies supported by specific noncovalent interactions such as multiple hydrogen bonds, which show drastic changes in their optical and electronic properties. [8] We report herein that the aggregation of cholesterolappended merocyanines with minor structural differences in various organic solvents results in the formation of organogels with dramatically different chromophore packing, thus giving rise to distinct optical properties through excitonic interactions.…”
mentioning
confidence: 92%
See 1 more Smart Citation
“…[7] Other examples include merocyanine assemblies supported by specific noncovalent interactions such as multiple hydrogen bonds, which show drastic changes in their optical and electronic properties. [8] We report herein that the aggregation of cholesterolappended merocyanines with minor structural differences in various organic solvents results in the formation of organogels with dramatically different chromophore packing, thus giving rise to distinct optical properties through excitonic interactions.…”
mentioning
confidence: 92%
“…[5] This structural character also makes these dyes attractive as supramolecular components because different chromophore packing or spatial arrangements result in prominent changes in their optical properties through excitonic interactions. [6][7][8] Covalently tethered merocyanine dimers are interesting examples in that their optical properties can be tuned through the control of the relative orientation of two merocyanine chromophores by selecting the media. [7] Other examples include merocyanine assemblies supported by specific noncovalent interactions such as multiple hydrogen bonds, which show drastic changes in their optical and electronic properties.…”
mentioning
confidence: 99%
“…[6] We herein report a supramolecular system where exciton interactions of chromogenic components can be controlled through the conformational change of photochromic components. Previous our study on supramolecular complexation between merocyanine dye 1 [7] (Figure 1 a) and bismelamine (BM) receptors [8] through multiple hydrogen bonds demonstrated that the oligomethylene linker length of the receptors can control the J-(BM3) and H-type (BM12) exciton interactions of 1 (Figure 1 b). [9] From the spectroscopic and the NMR studies, it was suggested that the formation of discrete oligomers (1 + BM3) and folded supramolecular polymers (1 + BM12) are responsible for such contrasting exciton interactions.…”
mentioning
confidence: 93%
“…[19] The assemblies, which are held together by 36 hydrogen bonds, are thermodynamically stable, even at a concentration of 5 mm. [20] The calix [4]arene dimelamine 1 was functionalized with octadecyl chains to promote the self-organization of the double-rosette assemblies into a liquid-crystalline phase. The long alkyl chains are connected to the terminal benzamide moieties of 1 to prevent their interference with the network of hydrogen bonds that holds the double rosette together.…”
mentioning
confidence: 99%
“…6 (1 mm in [D 8 ]toluene) at 298 K. shown). [20,22,23] The optically active double-rosette assemblies (with P or M helicity) exhibit a very strong induced CD signal at a wavelength of 350-250 nm, [20] owing to the dissymmetric arrangement of the many chromophoric units, whereas the building block 1 is nearly CD inactive. The intensity of the CD signal of 1 3 ·((R)-propCYA) 6 does not decrease after several thermal cycles, evidencing the high thermal stability of the assembly.…”
mentioning
confidence: 99%